2019
DOI: 10.1097/md.0000000000017298
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs2000999 in the haptoglobin gene with total cholesterol, HDL-C, and LDL-C levels in Mexican type 2 diabetes patients

Abstract: Recently, studies have shown significant association between the rs2000999 polymorphism in the haptoglobin-encoding gene (HP) and low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) levels, which are important risk factors for cardiovascular diseases. However, the association of rs2000999 with serum lipids in Latin American diabetic populations is still uncharacterized. Here, we analyzed the association of rs2000999 with TC, high-density lipoprotein cholesterol (HDL-C), and LDL-C levels in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…IR was an important factor for AAAs to regulate the initiation and development of NAFLD. Epidemiological studies showed that the intakes of AAAs were positively correlated with the increase of plasma LDL-C, which was an independent risk factor for IR [44][45][46]. In parallel, a cross-sectional study of 718 subjects indicated that AAAs was positively correlated with IR, X.Q.…”
Section: Discussionmentioning
confidence: 98%
“…IR was an important factor for AAAs to regulate the initiation and development of NAFLD. Epidemiological studies showed that the intakes of AAAs were positively correlated with the increase of plasma LDL-C, which was an independent risk factor for IR [44][45][46]. In parallel, a cross-sectional study of 718 subjects indicated that AAAs was positively correlated with IR, X.Q.…”
Section: Discussionmentioning
confidence: 98%
“…Dyslipidemia is a disorder of lipid metabolism and is defined by higher levels of TC, TG, and LDL-C as well as lower concentrations of HDL-C in the serum ( 25 ). Suarez-Sanchez et al ( 26 ) reported that a decrease in lipid levels of serum is associated with a reduced risk of metabolic diseases. Furthermore, Frohnert et al ( 27 ) showed that elevated serum NEFA levels can increase the risk of adiposity, insulin resistance, and angina pectoris.…”
Section: Discussionmentioning
confidence: 99%
“…We found that Arg supplementation had no effect on feed intake, feed conversion ratio, or growth performance, but reduced intraperitoneal fat mass in tilapia and the size of adipocyte, as compared with the control group. It has been reported that a decrease in plasma lipid levels is associated with reduced risk of metabolic Fads2, Δ4 fatty acyl desaturase 2; Δ5/Δ6 Fads2, Δ5/Δ6 fatty acyl desaturase 2; Elovl5, elongase 5 of very long-chain fatty acids; Hnf4α, hepatocyte nuclear factor 4α; Lxr, liver X receptor diseases [19]. Therefore, we determined serum lipid levels, including TG, TC, LDL, and HDL.…”
Section: Discussionmentioning
confidence: 99%